Communication Skills in Psychiatry: A Core Competency for Healthcare Professionals - Dr. Magesh Rajagopal (Tamil Psychiatry Journal, 2026)
In the medical field, especially in psychiatry, communication is essential. The ability to speak well and to listen and understand others is crucial for doctors and healthcare professionals. It is through effective communication and understanding that patients and their families develop trust in the treatment. It is a misconception that only those with a kind demeanor and good character can communicate effectively. Communication skills can be developed by anyone. This ability can be improved through teaching and proper training. Communication skills play a greater role than all other skills. Therefore, mental health professionals and doctors should pay close attention to developing this skill. This article discusses in detail the importance of developing good communication skills. The various components of communication and its barriers are also explained in detail. Practical tips for healthcare professionals to improve their communication is also discussed here.